Learning media development training through optimization of Microsoft PowerPoint - Yuwono, Muhammad Ridlo; Firmansah, Fery; Syaifuddin, M. Wahid; Yuliana, Yuliana (Universitas Muhammadiyah Magelang, 2021)
The purpose of this service is to optimize the use of ms. powerPoint for the development of innovative learning media. This training was held at SMP IT Ma'arif NU, Trucuk District, Klaten Regency, Central Java Province. This service was carried out by training methods on 1) making simple objects that can move automatically, 2) making countdowns, 3) making attractive template designs without downloading from the internet, and 4) making interactive practice questions. During the evaluation, participants were able to optimize Ms. PowerPoint for developing learning media.